“And God Remembered:” Barrenness and Hope in Genesis - Loumagne, Megan (Lumen et Vita, 2015)
For a book of beginnings,[1] Genesis is ironically replete with beginnings that almost were not. Indeed, the motif of the barren woman, the woman unable to produce a new beginning in the form of a child, is so common it becomes almost redundant in the narrative. What is most characteristic of God in Genesis—to be a fertile source of life[2]—is painfully denied the matriarchs. This pain is heightened by the steadily increasing tension in the text regarding the fulfillment of God’s covenant with Abraham. God’s promise to Abraham that he will be “a great nation”[3] with many descendants requires Abraham to have offspring in order for it to be fulfilled, yet nature repeatedly opposes the fulfillment of the promise. Through the repeated motif of the barrenness of the matriarchs, the reader is inducted into the struggle of the primary characters to have faith in a God “whose promise tarries too long.”[4] This paper examines the motif of barrenness in Genesis in order to argue that the barrenness of the matriarchs functions literarily as a “type-scene” that is meant to signify a complex series of messages in a few simple plot details. The motif also functions theologically. Through negative contrast, the barren wombs recall the goodness of creation as well as God’s nature as the fertile giver of life. Furthermore, the repetition of the motif in Genesis, far from indicating a lack of creativity on the part of the redactors, instead serves to inculcate through repetition an expectation in the reader that God will do what God always does in this situation—namely, bring life from death. The motif’s power is in its predictability. In this way, the motif of barrenness in Genesis is a tutor in the school of hope. [1] Jon D. Levenson. “Genesis: Introduction,” Jewish Study Bible, 8. [2] As Phyllis Trible notes in God and the Rhetoric of Sexuality (Philadelphia: Fortress Press, 1978), “making is a familiar activity for God,” 90. [3] Genesis 12:2, Jewish Study Bible, 30. [4] Victor Hamilton, The Book of Genesis: Chapter 1-17 (Grand Rapids, MI: W.B. Eerdmans, 1990), 151.